Close Friendship Strength and Broader Peer Group Desirability as Differential Predictors of Adult Mental Health. Issue 1 (21st August 2017) - Narr, Rachel K.; Allen, Joseph P.; Tan, Joseph S.; Loeb, Emily L.
Abstract : Middle adolescents' close friendship strength and the degree to which their broader peer group expressed a preference to affiliate with them were examined as predictors of relative change in depressive symptoms, self‐worth, and social anxiety symptoms from ages 15 to 25 using multimethod, longitudinal data from 169 adolescents. Close friendship strength in midadolescence predicted relative increases in self‐worth and decreases in anxiety and depressive symptoms by early adulthood. Affiliation preference by the broader peer group, in contrast, predicted higher social anxiety by early adulthood. Results are interpreted as suggesting that adolescents who prioritize forming close friendships are better situated to manage key social developmental tasks going forward than adolescents who prioritize attaining preference with many others in their peer milieu.